Analisis Hubungan dan Pengaruh Variabel â€œMarketing Mix 7Pâ€ terhadap Keputusan Memilih Perguruan Tinggi Swasta di Tangerang Raya - Paulus Yulius Fanggidae (Universitas PGRI Yogyakarta, 2023)
The challenges of today's higher education institutions, apart from the rapid environmental changes on one side and the other, are that universities must provide various facilities and infrastructure as well as attractive programs to support the process of